2022
DOI: 10.1183/13993003.02962-2021
|View full text |Cite
|
Sign up to set email alerts
|

Reference equations for evaluation of spirometry function tests in South Asia, and among South Asians living in other countries

Abstract: BackgroundThere is little data to accurate interpretation of spirometry data in South Asia, a major global region with high reported burden for chronic respiratory disease.MethodWe measured lung function in 7,453 healthy men and women aged over 18 years, from Bangladesh, North India, South India, Pakistan and Sri Lanka, as part of the South Asia Biobank study. We first assessed the accuracy of existing equations for predicting normal forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), and FEV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… 3 A recent study suggested higher accuracy when the information on region was added to the lung function reference equation. 26 In fact, our study showed considerable discrepancy in the predictive value of FEV 1 or COPD severity between global reference equation (GLI-2012) and region-specific reference equations (Choi’s and KHANES VI). One of the potential reasons for the discrepancy may be attributed to variations in human body proportions based on different ethnicities of GLI-2012 reference equation.…”
Section: Discussionmentioning
confidence: 53%
“… 3 A recent study suggested higher accuracy when the information on region was added to the lung function reference equation. 26 In fact, our study showed considerable discrepancy in the predictive value of FEV 1 or COPD severity between global reference equation (GLI-2012) and region-specific reference equations (Choi’s and KHANES VI). One of the potential reasons for the discrepancy may be attributed to variations in human body proportions based on different ethnicities of GLI-2012 reference equation.…”
Section: Discussionmentioning
confidence: 53%
“…In detecting the presence of bronchial asthma, health workers usually use a spirometer by measuring the volume in the FVC and FEV1 examinations [7] [8]. However, In providing services to patients with bronchial asthma not only requires this measurement alone as the only diagnostic tool, but health care providers need time to access to spirometer data and then follow up on symptoms and treatment schedules [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…4 Other key cohorts include the Singapore Preconception Study of Long-Term Maternal and Child Outcomes (S-PRESTO), the Singapore-Malaysia Cross Sectional Genetic Epidemiology Study (SMCGES) and the Health for Life in Singapore (HELIOS) study that have contributed to developing spirometry reference equations for South Asians and, demonstrated the additive climatic influence (beyond familial tendency) on risks of developing allergy, asthma and allergic rhinitis in our tropical climate. 5,6 With the ongoing transformational shift in national population health delivery through Healthier SG, the focus on preventative and proactive care needs to leverage on these established cohorts especially once chronic respiratory conditions such as asthma and COPD come onboard next year (2024). 7 A local lung cancer study demonstrated that many females and non-smokers diagnosed with lung cancer did not fit US National Lung Screening Trial criteria, a finding observed across other Asia Pacific countries.…”
mentioning
confidence: 99%

Letter from Singapore

Chotirmall,
Abisheganaden,
Chew
et al. 2023
Respirology
Self Cite